SOSIALISASI DAN BIMBINGAN BEROLAHRAGA PADA MASA PANDEMI COVID-19 BAGI GENERASI-Z DI KOTA PALANGKARAYA - Yudo - Harvianto (Universitas PGRI Semarang, 2020)
Exercise is an important as well as recommended activity during the current pandemic of Coronavirus Disease 2019 (Covid-19). Exercise is also a way to improve human’s body fitness and stamina, so that it will boost the immune system. Good immune system will fight the Covid-19 better, but the problem now is how to start new habits in order to avoid transmission of this deadly virus. Inevitably, people need to change to do the new habits in all aspects of life, such as in social, in economic, in education and in health. The habits should be adapted to the public health protocols including in doing daily exercises. In some places, there are still many z-generations who are doing exercise while avoiding to comply those health protocols required by the government. This means that the exercise they are doing is not safe for their health and can even harm themselves. Some examples are (1) using a mask when doing an intense exercise, (2) not maintaining the suggested distance when doing group exercise, and (3) not bringing drinks from home. The aim of this activity is for the millennial generation to do exercisr properly during the Covid-19 pandemic. The method used was a regular socialization and guidance in carrying out exercises during a pandemic in accordance with good and right health protocols. The result showed that participants have properly and correctly understood and applied the required health protocols while doing exercises during the pandemic.Keywords: Excersice, Health Protocols, Z-Generations